Transcriptional and post-translational control of chlorophyll biosynthesis by dark-operative protochlorophyllide oxidoreductase in Norway spruce - Stolárik, Tibor; Hedtke, Boris; Šantrůček, Jiří; Ilík, Petr; Grimm, Bernhard; Pavlovič, Andrej (Photosynthesis research, 2017)
Unlike angiosperms, gymnosperms use two different enzymes for the reduction of protochlorophyllide to chlorophyllide: the light-dependent protochlorophyllide oxidoreductase (LPOR) and the dark-operative protochlorophyllide oxidoreductase (DPOR). In this study, we examined the specific role of both enzymes for chlorophyll synthesis in response to different light/dark and temperature conditions at different developmental stages (cotyledons and needles) of Norway spruce (Picea abies Karst.). The accumulation of chlorophyll and chlorophyll-binding proteins strongly decreased during dark growth in secondary needles at room temperature as well as in cotyledons at low temperature (7 °C) indicating suppression of DPOR activity. The levels of the three DPOR subunits ChlL, ChlN, and ChlB and the transcripts of their encoding genes were diminished in dark-grown secondary needles. The low temperature had minor effects on the transcription and translation of these genes in cotyledons, which is suggestive for post-translational control in chlorophyll biosynthesis. Taking into account the higher solubility of oxygen at low temperature and oxygen sensitivity of DPOR, we mimicked low-temperature condition by the exposure of seedlings to higher oxygen content (33%). The treatment resulted in an etiolated phenotype of dark-grown seedlings, confirming an oxygen-dependent control of DPOR activity in spruce cotyledons. Moreover, light-dependent suppression of mRNA and protein level of DPOR subunits indicates that more efficiently operating LPOR takes over the DPOR function under light conditions, especially in secondary needles.
Keywords: Protochlorophyllide; Norsko; chlorofyl; Gene Expression Regulation, Plant; oxidoreduktasy působící na CH-CH vazby; Low temperature; Light; Picea; světlo; Oxidoreductases Acting on CH-CH Group Donors; Norway; Chill stress; DPOR; Norway spruce; Temperature; regulace genové exprese u rostlin; Chlorophyll; smrk; teplota